Biochar-LDH-nZVI-GO composite material for organic pollution remediation as well as preparation method and application of biochar-LDH-nZVI-GO composite material

By preparing biochar-LDH-nZVI-GO composite material, the problem of iron-based nanoparticle aggregation was solved, and efficient remediation of organic pollutants was achieved, especially the stable removal of trichloroethylene, chlorobenzene and polychlorinated biphenyls. It has good adsorption and degradation effects, and the material is readily available, low in cost and environmentally friendly.

CN121103320APending Publication Date: 2025-12-12山东省土壤污染防治中心
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202511508628.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing technologies are unable to effectively solve the problem of aggregation of iron-based nanoparticles, resulting in poor remediation effects on organic pollutants such as chlorinated hydrocarbons and benzene compounds.

Method used

A biochar-LDH-nZVI-GO composite material was prepared by reacting a biochar-Mg/Al-LDH-GO composite with FeSO4·7H2O to form a biochar-LDH-nZVI-GO composite material. The electronic conductivity of graphene oxide and the adsorption properties of biochar were utilized to achieve efficient remediation of organic pollutants.

Benefits of technology

It achieves efficient and stable removal of organic pollutants such as trichloroethylene, chlorobenzene and polychlorinated biphenyls, and has a good synergistic effect of adsorption-conduction-degradation. Moreover, the material is readily available, low in cost, and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121103320A_ABST
    Figure CN121103320A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of organic pollution treatment, and relates to a biochar-LDH-nZVI-GO composite material for organic pollution remediation and a preparation method and application thereof.The preparation method comprises the steps that graphene oxide is ultrasonically dispersed in deionized water, magnesium salt and aluminum salt are added to form uniform suspension liquid, then the uniform suspension liquid is mixed with biochar suspension liquid, and the biochar-nZVI-GO composite material is obtained; carrying out pH (Potential of Hydrogen) regulation and a hydrothermal crystallization reaction, so as to prepare a biochar-Mg / Al-LDH-GO compound; and dispersing the compound in an organic solvent, sequentially adding FeSO4. 7H2O and a NaBH4 solution in an inert atmosphere to carry out a reduction reaction, and finally washing and drying to obtain the biochar-LDH-nZVI-GO composite material. The material shows high-efficiency removal capacity on various organic pollutants such as trichloroethylene, chlorobenzene and polychlorinated biphenyl, is suitable for high-efficiency green remediation of organic pollutants in soil and water, and has good popularization and application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of organic pollution treatment, and relates to a biochar composite material for organic pollution remediation and a preparation and application thereof. BACKGROUND

[0002] Organic pollutants are one of the main environmental pollutants, and there are many types of organic pollutants in the environment, such as halogenated hydrocarbons, polychlorinated biphenyls, polycyclic aromatic hydrocarbons, azo dyes, pesticides and the like, and most of the persistent organic pollutants have high toxicity.

[0003] Biochar is a new type of material, which is a product formed by pyrolysis of biomass under anaerobic conditions. Biochar has small particles, fine distribution and light texture, and is a black porous solid, and the main elements are carbon and oxygen. The content of carbon in biochar is generally more than 70%, and the raw materials for preparing biochar are widely available, such as sawdust, straw, industrial organic waste, municipal sludge, palm fiber and coconut fiber. SUMMARY

[0004] The purpose of the present application is to provide a biochar-LDH-nZVI-GO composite material for organic pollution remediation, wherein the biochar-LDH-nZVI-GO composite material can effectively solve the problem of agglomeration and passivation of iron-based nanoparticles, and improve the remediation effect on organic pollution such as chlorinated hydrocarbons and benzene series.

[0005] To achieve the above-mentioned purpose, the present application adopts the following technical solutions:

[0006] Specifically, the present application provides a biochar-LDH-nZVI-GO composite material for organic pollution remediation, and the preparation method of the biochar-LDH-nZVI-GO composite material comprises the following steps:

[0007] 1) Preparation of biochar-Mg / Al-LDH-GO complex: Graphene oxide was added to deionized water and sonicated for 30 minutes. Then, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were added and stirred to form a homogeneous suspension. The suspension was then added to deionized water containing biochar, the pH was adjusted, and the crystallization reaction was carried out in a water bath. The precipitate was collected by centrifugation, washed, and dried to obtain the biochar-Mg / Al-LDH-GO complex.

[0008] 2) Preparation of biochar-LDH-nZVI-GO composite material: The biochar-Mg / Al-LDH-GO composite material prepared in step 1) was dispersed in an organic solvent, ultrasonically treated, and FeSO4·7H2O was slowly added while stirring vigorously. NaBH4 solution was slowly added dropwise to the system. After the addition was completed, the reaction continued. The final product was washed and vacuum dried to obtain the biochar-LDH-nZVI-GO composite material.

[0009] Furthermore, the method for preparing deionized water containing biochar according to the present invention is as follows: 1g of biochar is added to 50-80ml of deionized water to obtain a suspension A containing biochar.

[0010] Further, the preparation method of the biochar of the present invention is as follows: the washed corn stalks are dried, crushed, placed in a muffle furnace, heated to 400℃-450℃ at a rate of 10-15℃ / min under N2 atmosphere, and pyrolyzed with limited oxygen for 2-4 hours. After cooling, the biochar is ground and passed through a 200-mesh sieve, and dried at 70-80℃ to obtain the biochar. More preferably, the preparation method of the biochar is as follows: the washed corn stalks are dried, crushed, placed in a muffle furnace, heated to 425℃ at a rate of 12℃ / min under N2 atmosphere, and pyrolyzed with limited oxygen for 4 hours. After cooling, the biochar is ground and passed through a 200-mesh sieve, and dried at 70℃.

[0011] Further, the organic solvent described in this invention is a mixture of ethanol, isopropanol and water, and the ratio of the three components, calculated as a percentage, is 60-80: 3-7: 13-37; more preferably, the ratio of the three components is 70: 5: 25.

[0012] Further, the weight ratio of Mg(NO3)2·6H2O:Al(NO3)3·9H2O:graphene oxide:biochar in this invention is 100-200:50-100:1-5:10; more preferably, the weight ratio of Mg(NO3)2·6H2O:Al(NO3)3·9H2O:graphene oxide:biochar is 154:75:3:10.

[0013] Further, the pH value of the present invention is 9.5-10.5, and the regulator is selected from sodium hydroxide, potassium hydroxide, ammonia, urea or sodium bicarbonate-sodium carbonate buffer solution. More preferably, the regulator is selected from sodium hydroxide or sodium bicarbonate-sodium carbonate buffer solution, and the pH value is 10.0.

[0014] Furthermore, the organic solvent of the present invention is a mixture of ethanol, isopropanol and water in a percentage ratio of 70:5:25; the weight ratio of Mg(NO3)2·6H2O:Al(NO3)3·9H2O:graphene oxide is 154:75:3; the regulator is selected from sodium bicarbonate-sodium carbonate buffer solution, and the pH value is 10.0.

[0015] 1) Preparation of graphene oxide: Under vigorous stirring in an ice-water bath, natural graphite powder and NaNO3 were slowly added to concentrated H2SO4; then KMnO4 was slowly added in portions. After removing the ice bath at below 20°C, the reaction was carried out at 35°C for 2 hours. Deionized water was then slowly added and the temperature was raised to 98°C and maintained for 30 minutes. After the reaction was terminated, deionized water and 30% H2O2 were added until the solution turned bright yellow. After the reaction solution was cooled to room temperature, the obtained product was transferred to a centrifuge tube and washed repeatedly by alternating centrifugation with 5% dilute hydrochloric acid solution and deionized water until the pH of the supernatant was close to neutral. The washed GO gel precipitate was freeze-dried to obtain graphene oxide.

[0016] 2) Preparation of solution B: Measure 40 mL of deionized water and add 0.03 g of graphene oxide to it. Sonicate for 30 minutes to obtain GO suspension. Add 1.54 g of Mg(NO3)2·6H2O and 0.75 g of Al(NO3)3·9H2O in sequence while stirring slowly. Continue stirring until the solution is evenly dissolved to obtain suspension B for later use.

[0017] 3) Preparation of biochar-Mg / Al-LDH-GO complex: Suspension B was slowly added dropwise to suspension A which was being vigorously stirred. The pH of the mixture was adjusted to 10.0 with sodium bicarbonate-sodium carbonate buffer solution. The mixture was then crystallized in a water bath at 60-70℃ for 20-28 hours under nitrogen protection. After the reaction was completed, the precipitate was collected by centrifugation and washed 2-3 times alternately with deionized water and anhydrous ethanol. The precipitate was then dried in a vacuum drying oven at 55-65℃ for 10-15 hours to obtain the biochar-Mg / Al-LDH-GO complex.

[0018] 4) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 70% ethanol and 5% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of FeSO4·7H2O to the suspension C and stir vigorously, and slowly add 1.0 mol / L NaBH4 to the system dropwise. React for 0.5-1.5 h, wash 2-4 times with anhydrous ethanol, and then vacuum dry at 55-65℃ to obtain the final product.

[0019] Furthermore, the present invention relates to the application of the biochar-LDH-nZVI-GO composite material in the in-situ remediation of organic pollution in soil or water.

[0020] Furthermore, the organic pollution described in this invention is halogenated hydrocarbon and / or benzene series pollution; further, the halogenated hydrocarbon is trichloroethylene, and the benzene series is chlorobenzene and / or polychlorinated biphenyls.

[0021] The present invention has achieved unexpected technical effects, as detailed below:

[0022] 1) Compared with the prior art, the biochar-LDH-nZVI-GO composite material provided by the present invention has a high efficiency and stable removal capacity for organic pollutants, especially for a variety of typical organic pollutants such as trichloroethylene, chlorobenzene and polychlorinated biphenyls. Its unique "adsorption-conduction-degradation" synergistic mechanism overcomes the limitation of the single function of traditional materials.

[0023] 2) This invention uses waste straw as raw material to prepare biochar matrix, realizing the high-value-added resource recycling of agricultural waste. The entire material system is environmentally friendly, and due to its high catalytic activity, it requires a small amount, effectively reducing the secondary environmental risks and overall costs of the remediation process.

[0024] 3) Soil experiments revealed that the composite material of the present invention not only has high remediation efficiency and a wide range of applicable pollutants, but also has the characteristics of readily available raw materials, controllable process, and economical cost, and has broad market prospects and social benefits. Attached Figure Description

[0025] Figure 1 The removal effect of biochar-LDH-nZVI composite materials on trichloroethylene in Examples 5-8 and Comparative Examples 1-8.

[0026] Figure 2 The removal effect of biochar-LDH-nZVI composite materials on polychlorinated biphenyls in Examples 5-8 and Comparative Examples 1-8.

[0027] Figure 3The removal effect of biochar-LDH-nZVI composite materials on chlorobenzene in Examples 5-8 and Comparative Examples 1-8. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. Unless otherwise specified, the experimental reagents used in the following embodiments are all conventional biochemical reagents; and the experimental methods described are all conventional methods unless otherwise specified.

[0029] In this invention, GO stands for graphene oxide.

[0030] Example 1: A biochar and its suspension for the remediation of organic pollution, the preparation method of which is as follows:

[0031] The washed corn stalks are dried, crushed, and placed in a muffle furnace. Under a N2 atmosphere, they are heated to 420°C at a rate of 12°C / min and subjected to oxygen-limited pyrolysis for 2-4 hours. After cooling, they are ground and passed through a 200-mesh sieve, and then dried at 75°C to obtain the biochar. More preferably, the preparation method of the biochar is as follows: The washed corn stalks are dried, crushed, and placed in a muffle furnace. Under a N2 atmosphere, they are heated to 425°C at a rate of 12°C / min and subjected to oxygen-limited pyrolysis for 4 hours. After cooling, they are ground and passed through a 200-mesh sieve, and then dried at 70°C.

[0032] Dissolve 0.1g of the prepared biochar in 65ml of deionized water for later use.

[0033] Example 2: A biochar for the remediation of organic pollution, the preparation method of which is as follows:

[0034] The washed corn stalks are dried, crushed, and placed in a muffle furnace. Under a N2 atmosphere, they are heated to 400°C at a rate of 10°C / min and subjected to oxygen-limited pyrolysis for 2 hours. After cooling, they are ground and passed through a 200-mesh sieve, and then dried at 70°C to obtain the biochar. More preferably, the preparation method of the biochar is as follows: The washed corn stalks are dried, crushed, and placed in a muffle furnace. Under a N2 atmosphere, they are heated to 425°C at a rate of 12°C / min and subjected to oxygen-limited pyrolysis for 4 hours. After cooling, they are ground and passed through a 200-mesh sieve, and then dried at 70°C.

[0035] Dissolve 0.1g of the prepared biochar in 50ml of deionized water for later use.

[0036] Example 3: A biochar for the remediation of organic pollution, the preparation method of which is as follows:

[0037] The washed corn stalks are dried, crushed, and placed in a muffle furnace. Under a N2 atmosphere, they are heated to 450°C at a rate of 15°C / min and subjected to oxygen-limited pyrolysis for 2-4 hours. After cooling, they are ground and passed through a 200-mesh sieve, and then dried at 80°C to obtain the biochar. More preferably, the preparation method of the biochar is as follows: The washed corn stalks are dried, crushed, and placed in a muffle furnace. Under a N2 atmosphere, they are heated to 425°C at a rate of 12°C / min and subjected to oxygen-limited pyrolysis for 4 hours. After cooling, they are ground and passed through a 200-mesh sieve, and then dried at 70°C.

[0038] Dissolve 0.1g of the prepared biochar in 80ml of deionized water for later use.

[0039] Example 4: A graphene oxide for the remediation of organic pollution, the preparation method of which is as follows:

[0040] Under vigorous stirring in an ice-water bath, natural graphite powder and NaNO3 were slowly added to concentrated H2SO4; then KMnO4 was slowly added in portions. After removing the ice bath at below 20°C, the reaction was carried out at 35°C for 2 hours. Deionized water was then slowly added and the temperature was raised to 98°C and maintained for 30 minutes. After the reaction was terminated, deionized water and 30% H2O2 were added until the solution turned bright yellow. After the reaction solution was cooled to room temperature, the obtained product was transferred to a centrifuge tube and washed repeatedly by alternating centrifugation with dilute hydrochloric acid solution and deionized water. The washed GO gel precipitate was freeze-dried to obtain graphene oxide.

[0041] Example 5: Preparation of a biochar-LDH-nZVI-GO composite material for organic pollution remediation, the preparation method of which is as follows:

[0042] 1) Add 0.03g of graphene oxide to 40mL of deionized water and sonicate for 30 minutes to obtain GO suspension. Add 1.54g of Mg(NO3)2·6H2O and 0.75g of Al(NO3)3·9H2O in sequence while stirring slowly and continuously. Continue stirring until the solution is uniformly dissolved to obtain suspension B, which is ready for use.

[0043] 2) Preparation of biochar-Mg / Al-LDH-GO complex: Suspension B was slowly added dropwise to the suspension of Example 1 which was being vigorously stirred. The pH of the mixture was adjusted to 10.0 with sodium bicarbonate-sodium carbonate buffer solution. The mixture was then crystallized in a water bath at 65°C for 24 hours under nitrogen protection. After the reaction was completed, the precipitate was collected by centrifugation and washed three times alternately with deionized water and anhydrous ethanol. The precipitate was then dried in a vacuum drying oven at 60°C for 12 hours to obtain the biochar-Mg / Al-LDH-GO complex.

[0044] 3) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 70% ethanol and 5% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to the suspension C and stir vigorously. Slowly add 1.0mol / L NaBH4 to the system until excess (at least 1.5ml), react for 1h, wash 3 times with anhydrous ethanol, and dry under vacuum at 60℃ to obtain the final product.

[0045] Example 6: Preparation of a biochar-LDH-nZVI-GO composite material for organic pollution remediation, the preparation method of which is as follows:

[0046] 1) Add 0.01g of graphene oxide to 40mL of deionized water and sonicate for 30 minutes to obtain GO suspension. Add 1g of Mg(NO3)2·6H2O and 0.5g of Al(NO3)3·9H2O in sequence while stirring slowly and continuously. Continue stirring until the solution is uniformly dissolved to obtain suspension B, which is ready for use.

[0047] 2) Preparation of biochar-Mg / Al-LDH-GO complex: Suspension B was slowly added dropwise to the suspension of Example 2 which was being vigorously stirred. The pH of the mixture was adjusted to 9.5 with sodium bicarbonate-sodium carbonate buffer solution. The mixture was then crystallized in a water bath at 60°C for 20 hours under nitrogen protection. After the reaction was completed, the precipitate was collected by centrifugation and washed twice with deionized water and anhydrous ethanol alternately. The precipitate was then dried in a vacuum drying oven at 55°C for 10 hours to obtain the biochar-Mg / Al-LDH-GO complex.

[0048] 3) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 60% ethanol and 3% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to the suspension C and stir vigorously. Slowly add 1.0mol / L NaBH4 to the system until excess (at least 1.5ml), react for 0.5h, wash twice with anhydrous ethanol, and then vacuum dry at 55℃ to obtain the final product.

[0049] Example 7: Preparation of a biochar-LDH-nZVI-GO composite material for organic pollution remediation, the preparation method of which is as follows:

[0050] 1) Add 0.05g of graphene oxide to 40mL of deionized water and sonicate for 30 minutes to obtain GO suspension. Add 2g of Mg(NO3)2·6H2O and 1g of Al(NO3)3·9H2O in sequence while stirring slowly and continuously. Continue stirring until the solution is uniformly dissolved to obtain suspension B, which is ready for use.

[0051] 2) Preparation of biochar-Mg / Al-LDH-GO complex: Suspension B was slowly added dropwise to the suspension of Example 3 which was being vigorously stirred. The pH of the mixture was adjusted to 10.0 with sodium bicarbonate-sodium carbonate buffer solution. The mixture was then crystallized in a water bath at 70°C for 28 hours under nitrogen protection. After the reaction was completed, the precipitate was collected by centrifugation and washed three times alternately with deionized water and anhydrous ethanol. The precipitate was then dried in a vacuum drying oven at 65°C for 15 hours to obtain the biochar-Mg / Al-LDH-GO complex.

[0052] 3) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 80% ethanol and 7% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to the suspension C and stir vigorously, slowly add 1.0mol / L NaBH4 to the system until excess (at least 1.5ml), react for 0.5-1.5h, wash 2-4 times with anhydrous ethanol, and then vacuum dry at 55-65℃ to obtain the final product.

[0053] Example 8: Preparation of a biochar-LDH-nZVI-GO composite material for organic pollution remediation, the preparation method of which is as follows:

[0054] 1) Add 0.03g of graphene oxide to 40mL of deionized water and sonicate for 30 minutes to obtain GO suspension. Add 1.54g of Mg(NO3)2·6H2O and 0.75g of Al(NO3)3·9H2O in sequence while stirring slowly and continuously. Continue stirring until the solution is uniformly dissolved to obtain suspension B, which is ready for use.

[0055] 2) Preparation of biochar-Mg / Al-LDH-GO complex: Suspension B was slowly added dropwise to the suspension of Example 1 under vigorous stirring. The pH was adjusted to 10.0 with sodium hydroxide. Under nitrogen protection, the crystallization reaction was carried out in a water bath at 60-70℃ for 20-28 hours. After the reaction was completed, the precipitate was collected by centrifugation and washed 2-3 times alternately with deionized water and anhydrous ethanol. The precipitate was dried in a vacuum drying oven at 55-65℃ for 10-15 hours to obtain biochar-Mg / Al-LDH-GO complex.

[0056] 3) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 70% ethanol and 5% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to the suspension C and stir vigorously, slowly add 1.0mol / L NaBH4 to the system until excess (at least 2.0ml), react for 0.5-1.5h, wash 2-4 times with anhydrous ethanol, and then vacuum dry at 55-65℃ to obtain the final product.

[0057] Comparative Example 1: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0058] Step 1) does not contain graphene oxide, and the final product is a biochar-LDH-nZVI composite material.

[0059] The other steps are the same as described in Example 5.

[0060] Comparative Example 2: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0061] Step 1) does not contain Mg(NO3)2·6H2O, and the final product is a biochar-LDH-nZVI composite material. The other steps are the same as described in Example 5.

[0062] Comparative Example 3: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0063] Step 1) does not contain Al(NO3)3·9H2O, and the final product is biochar-LDH-nZVI composite material.

[0064] The other steps are the same as described in Example 5.

[0065] Comparative Example 4: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0066] 1) Add 0.01g of graphene oxide to 40mL of deionized water and sonicate for 30 minutes to obtain GO suspension. Add 1.54g of Mg(NO3)2·6H2O and 0.75g of Al(NO3)3·9H2O in sequence while stirring slowly and continuously. Continue stirring until the solution is uniformly dissolved to obtain suspension B, which is ready for use.

[0067] The other steps are the same as described in Example 5.

[0068] Comparative Example 5: A biochar-LDH-nZVI composite material for the remediation of organic pollution, prepared by the following method:

[0069] The washed corn stalks were dried, crushed, and placed in a muffle furnace. Under a nitrogen atmosphere, they were heated to 420°C at a rate of 15°C / min and subjected to oxygen-limited pyrolysis for 3 hours. After cooling, they were ground and passed through a 200-mesh sieve and dried at 75°C to obtain biochar.

[0070] Biochar and α-Fe2O3 were mixed in a mass ratio of 6:1, and ultrasonically treated for 25 min at an ultrasonic power of 350 W. The mixture was then treated with an ultra-high pressure microfluidic homogenizer for 4 min at a pressure of 160 MPa and a temperature of 25 °C to obtain a biochar-LDH-nZVI composite material containing biochar-Fe2O3.

[0071] Comparative Example 6: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0072] 1) Add 1.54g of Mg(NO3)2·6H2O, 0.75g of Al(NO3)3·9H2O and 0.03g of graphene oxide to 40mL of deionized water, sonicate for 30 minutes to obtain GO suspension, continue stirring until dissolved evenly to obtain suspension B, for later use.

[0073] 2) Preparation of biochar-Mg / Al-LDH-GO complex: The suspension of Example 1 was slowly added dropwise to suspension B under vigorous stirring. The pH of the mixture was adjusted to 10.0 with sodium bicarbonate-sodium carbonate buffer solution. The mixture was crystallized in a water bath at 50°C for 10 hours under nitrogen protection. After the reaction was completed, the precipitate was collected by centrifugation and washed 4 times alternately with deionized water and anhydrous ethanol. The precipitate was dried in a vacuum drying oven at 60°C for 12 hours to obtain the biochar-Mg / Al-LDH-GO complex.

[0074] 3) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 70% ethanol and 5% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to the suspension C and stir vigorously. Slowly add 1.0mol / L NaBH4 to the system until excess (at least 1.5ml), react for 1h, wash 3 times with anhydrous ethanol, and dry under vacuum at 60℃ to obtain the final product.

[0075] Comparative Example 7: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0076] Preparation of biochar-LDH-nZVI-GO composite material: Take biochar-Mg / Al-LDH-GO composite material, disperse it in a mixed aqueous solvent of 85% ethanol and 10% isopropanol, and sonicate it to form a uniform suspension C; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to suspension C and stir vigorously. Slowly add 1.0mol / L NaBH4 to the system until it is in excess (at least 1.5ml), react for 0.5-1.5h, wash 2-4 times with anhydrous ethanol, and then vacuum dry at 55-65℃ to obtain the final product.

[0077] The other steps are the same as described in Example 5.

[0078] Comparative Example 8: Preparation of a biochar-LDH-nZVI composite material for organic pollution remediation, the preparation method of which is as follows:

[0079] Preparation of biochar-LDH-nZVI-GO composite material: Take biochar-Mg / Al-LDH-GO composite material, disperse it in a mixed aqueous solvent of 70% ethanol and 5% benzyl alcohol, and sonicate it to form a uniform suspension C; under nitrogen protection and ice-water bath, slowly add an appropriate amount of 0.1g FeSO4·7H2O to suspension C and stir vigorously. Slowly add 1.0mol / L NaBH4 to the system until excess (at least 2.0ml), react for 0.5-1.5h, wash 2-4 times with anhydrous ethanol, and vacuum dry at 55-65℃ to obtain the final product.

[0080] The other steps are the same as described in Example 5.

[0081] I. The effect of the biochar-LDH-nZVI composite material of the present invention on the removal of trichloroethylene

[0082] 1. Solution preparation

[0083] Prepare a trichloroethylene solution with an initial concentration of 10 mg / L.

[0084] 2. Experimental Procedure

[0085] Under anaerobic conditions, the biochar-LDH-nZVI composite materials from Examples 5-8 and Comparative Examples 1-8 were added to reaction flasks containing trichloroethylene solution, with a dosage of 0.8 g / L. The reaction flasks were placed on a 25°C constant-temperature shaker at 70 rpm for dechlorination reaction. Every 20 min, 100 μL of gas was taken from the headspace using a sampling needle, and the trichloroethylene content in the system was determined by gas chromatography to calculate the removal rate.

[0086] 3. Selection of composite materials

[0087] Biochar-LDH-nZVI composite materials of Examples 5-8 and Comparative Examples 1-8.

[0088] 4. Data processing and statistical processing

[0089] Sample measurements were repeated three times, and results are expressed as mean ± standard deviation. One-way ANOVA was performed using Graptop PRISM 6.0 to analyze the significant differences in soil PCB removal rates among treatment groups; p < 0.05 indicated a significant difference.

[0090] 5. Results Analysis

[0091] Figure 1 The removal effect of biochar-LDH-nZVI composite materials on trichloroethylene in Examples 5-8 and Comparative Examples 1-8.

[0092] Figure 1 The biochar-LDH-nZVI composite materials in Examples 5-8 showed significant removal efficiency of trichloroethylene, reaching 100% in 100 minutes. The composite materials in the comparative examples showed some removal effect on trichloroethylene. After 100 minutes of treatment, the specific analysis is as follows: Compared with Examples 5-8, which effectively removed trichloroethylene, the comparative examples were less effective due to their structural defects. Comparative Example 1 lacked graphene oxide, resulting in a loss of the electron conduction network and a slower nZVI degradation rate. Comparative Examples 2 and 3, lacking magnesium or aluminum salts, could not form a complete LDH layered structure, severely weakening their enrichment of pollutants and stabilization of nZVI. Comparative Example 4, due to an incorrect preparation sequence, caused GO agglomeration, failing to form an effective synergistic interface. Comparative Example 5, consisting only of physically mixed Fe2O3, had a weakened efficient reduction and dechlorination capacity. Comparative Examples 6, 7, and 8, due to insufficient crystallization temperature, excessively short reaction time, or the use of inappropriate benzyl alcohol solvent, respectively resulted in poor LDH crystallinity, incomplete nZVI formation, or damage to the LDH layers. Ultimately, all these factors led to a significantly lower synergistic effect of the composite materials on the adsorption and degradation of trichloroethylene compared to Examples 5-8.

[0093] II. The Removal Effect of the Biochar-LDH-nZVI Composite Material of the Present Invention on Polychlorinated Biphenyls

[0094] 1. Methods and Materials

[0095] The tested soil was derived from the topsoil of agricultural land. It was air-dried indoors, and impurities such as gravel and plant and animal remains were removed. The soil was then ground to a diameter of less than 60 mesh. The soil was yellow soil, composed of 11.0% sandy soil, 86.3% silt, and 2.7% clay. The organic matter content was 3.6%, the pH value was 6.4, and the water holding capacity was 51.1%.

[0096] Preparation method for polychlorinated biphenyl contaminated soil: Dilute 1 mL of 2,4,4-trichlorobiphenyl (1 g / L) with 5 mL of acetone and add it to 10 g of clean soil; after the acetone has completely evaporated, mix it thoroughly with another 990 g of clean soil and let it stand for 24 h to obtain 1 mg / kg 2,4,4-trichlorobiphenyl contaminated soil.

[0097] A blank treatment group without any treatment was set up; the above soil was treated with the biochar-LDH-nZVI composite material of Examples 5-8 and Comparative Examples 1-8.

[0098] 0.50g of the biochar-LDH-nZVI composite material from Examples 5-8 and Comparative Examples 1-8 were added to 500g of contaminated soil and thoroughly mixed by mechanical stirring to achieve a concentration of 1.0g / kg of biochar-LDH-nZVI composite material in the soil. The treatment lasted for 4 days, and then the removal rate of polychlorinated biphenyls (PCBs) in the soil by the biochar-LDH-nZVI composite material was calculated.

[0099] 2. Data processing and statistical processing

[0100] Sample measurements were repeated three times, and results are expressed as mean ± standard deviation. One-way ANOVA was performed using Graptop PRISM 6.0 to analyze the significant differences in soil PCB removal rates among treatment groups; p < 0.05 indicated a significant difference.

[0101] 3. Results Analysis

[0102] Figure 2 The removal efficiency of biochar-LDH-nZVI composite materials for polychlorinated biphenyls in Examples 5-8 and Comparative Examples 1-8

[0103] Polychlorinated biphenyls (PCBs) have larger molecular structures, stronger hydrophobicity, and higher chlorine substitution degrees, making their removal more dependent on the material's ability to accumulate pollutants and the efficiency of staged dechlorination. For example... Figure 2As shown, in the blank treatment group, the average removal efficiency of PCBs in the soil was low, only 5.3%, indicating that the volatilization or microbial degradation of PCBs under natural conditions was very limited. Specifically, Examples 5-8 showed significant differences compared to Comparative Examples 1-6 and Comparative Example 8 (p<0.01), Example 5 showed a significant difference compared to Comparative Example 7 (p<0.05), while Examples 6-8 did not show significant differences compared to Comparative Example 7 (p>0.05). The comparative examples all suffered from incomplete functionality or significantly lower performance than the experimental results of Examples 5-8 due to the absence of key components or defects in the preparation process. For example, the lack of an electron conduction medium (Comparative Example 1), incomplete LDH structure (Comparative Examples 2 and 3), interfacial recombination failure (Comparative Example 4), and insufficient active sites (Comparative Examples 5-8) all significantly hindered the material's adsorption capacity or degradation efficiency, preventing the synergistic removal effect of rapid enrichment and deep dechlorination of PCBs as seen in Examples 5-8.

[0104] III. The Removal Effect of the Biochar-LDH-nZVI Composite Material of the Present Invention on Chlorobenzene

[0105] 1. Reagent preparation

[0106] Prepare a single chlorobenzene solution with a concentration of 100 mg / L by yourself;

[0107] 2. Experimental Procedure

[0108] The above-mentioned soil was treated with biochar-LDH-nZVI composite materials from Examples 5-8 and Comparative Examples 1-8. Under anaerobic conditions, the biochar-LDH-nZVI composite materials from Examples 5-8 and Comparative Examples 1-8 were added to reaction flasks containing chlorobenzene solution. The dosage of the biochar-LDH-nZVI composite material was 1.0 g / L. The reaction flasks were placed on a 25°C constant-temperature shaker at 70 rpm for dechlorination reaction. After 100 min, the chlorobenzene in the system was determined by liquid chromatography, and the removal rate was calculated. The removal results are shown below. Figure 3 As shown.

[0109] 2. Statistical Analysis

[0110] Sample measurements were repeated five times, and results are expressed as mean ± standard deviation. One-way ANOVA was performed using Grappad PRISM 6.0 to analyze the significant differences in soil PCB removal rates among treatment groups; p < 0.05 indicated a significant difference.

[0111] 3. Results Analysis

[0112] Figure 3It can be seen that Examples 5-8 exhibit the best chlorobenzene removal effect: LDH initially captures chlorobenzene through ion-dipole interactions, while the biochar-GO composite network achieves specific adsorption and enrichment through π-π stacking, and finally, highly dispersed nZVI completes interfacial reduction and dechlorination. In contrast, Comparative Example 1 lacks π-π interactions of GO, resulting in insufficient adsorption capacity; Comparative Examples 2 and 3 have weakened initial capture capabilities due to LDH structural defects; Comparative Example 4 suffers from GO aggregation causing adsorption-degradation interface failure; Comparative Example 5 can only perform physical adsorption due to the absence of active nZVI; and Comparative Examples 6-8, due to incomplete structures, solvent damage, or different processes, cannot establish this synergistic mechanism of stepwise capture and targeted degradation, resulting in a significant reduction in chlorobenzene removal efficiency. Therefore, it can be seen that Examples 5-8 have a significantly better chlorobenzene removal effect than Comparative Examples 1-8.

[0113] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.

[0114] This invention is intended to cover all such substitutions, modifications, and variations that fall within the broad scope of the appended claims. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the scope of protection of this invention.

Claims

1. A biochar-LDH-nZVI-GO composite material for the remediation of organic pollution, characterized in that, The preparation method of the biochar-LDH-nZVI-GO composite material includes the following steps: 1) Preparation of biochar-Mg / Al-LDH-GO complex: Graphene oxide was added to deionized water and sonicated for 30 minutes. Then, Mg(NO3)2·6H2O and Al(NO3)3·9H2O were added and stirred to form a homogeneous suspension. The suspension was then added to deionized water containing biochar, the pH was adjusted, and the crystallization reaction was carried out in a water bath. The precipitate was collected by centrifugation, washed, and dried to obtain the biochar-Mg / Al-LDH-GO complex. 2) Preparation of biochar-LDH-nZVI-GO composite material: The biochar-Mg / Al-LDH-GO composite material prepared in step 1) was dispersed in an organic solvent, ultrasonically treated, and FeSO4·7H2O was slowly added while stirring vigorously. NaBH4 solution was slowly added dropwise to the system. After the addition was completed, the reaction continued. The final product was washed and vacuum dried to obtain the biochar-LDH-nZVI-GO composite material.

2. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, The method for preparing deionized water containing biochar is as follows: 1g of biochar is added to 50-80ml of deionized water to obtain a suspension A containing biochar.

3. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, The preparation method of the biochar is as follows: the washed corn stalks are dried, crushed, placed in a muffle furnace, heated to 400℃-450℃ at a rate of 10-15℃ / min under N2 atmosphere, and pyrolyzed with limited oxygen for 2-4 hours. After cooling, the biochar is ground through a 200-mesh sieve and dried at 70-80℃. More preferably, the preparation method of the biochar is as follows: the washed corn stalks are dried, crushed, placed in a muffle furnace, heated to 425℃ at a rate of 12℃ / min under N2 atmosphere, and pyrolyzed with limited oxygen for 4 hours. After cooling, the biochar is ground through a 200-mesh sieve and dried at 70℃.

4. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, The organic solvent is a mixture of ethanol, isopropanol and water, and the ratio of the three components is 60-80:3-7:13-37; more preferably, the ratio of the three components is 70:5:

25.

5. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, The weight ratio of Mg(NO3)2·6H2O:Al(NO3)3·9H2O:graphene oxide:biochar is 100-200:50-100:1-5:10; more preferably, the weight ratio of Mg(NO3)2·6H2O:Al(NO3)3·9H2O:graphene oxide:biochar is 154:75:3:

10.

6. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, The pH value is 9.5-10.5, and the regulator is selected from sodium hydroxide, potassium hydroxide, ammonia, urea or sodium bicarbonate-sodium carbonate buffer solution. More preferably, the regulator is selected from sodium hydroxide or sodium bicarbonate-sodium carbonate buffer solution, and the pH value is 10.

0.

7. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, The organic solvent is a mixture of ethanol, isopropanol, and water in a percentage ratio of 70:5:25; the weight ratio of Mg(NO3)2·6H2O:Al(NO3)3·9H2O:graphene oxide is 154:75:3; the regulator is selected from sodium bicarbonate-sodium carbonate buffer solution, and the pH value is 10.

0.

8. The biochar-LDH-nZVI-GO composite material for organic pollution remediation according to claim 1, characterized in that, 1) Preparation of graphene oxide: Under vigorous stirring in an ice-water bath, natural graphite powder and NaNO3 were slowly added to concentrated H2SO4; then KMnO4 was slowly added in portions. After removing the ice bath at below 20°C, the reaction was carried out at 35°C for 2 hours. Deionized water was then slowly added and the temperature was raised to 98°C and maintained for 30 minutes. After the reaction was terminated, deionized water and 30% H2O2 were added until the solution turned bright yellow. After the reaction solution was cooled to room temperature, the obtained product was transferred to a centrifuge tube and washed repeatedly by alternating centrifugation with 5% dilute hydrochloric acid solution and deionized water until the pH of the supernatant was close to neutral. The washed GO gel precipitate was freeze-dried to obtain graphene oxide. 2) Preparation of solution B: Measure 40 mL of deionized water and add 0.03 g of graphene oxide to it. The GO suspension was obtained by ultrasonic treatment for 30 minutes. 1.54 g of Mg(NO3)2·6H2O and 0.75 g of Al(NO3)3·9H2O were added sequentially with continuous slow stirring. The mixture was stirred until it was dissolved evenly to obtain suspension B, which was set aside for later use. 3) Preparation of biochar-Mg / Al-LDH-GO complex: Suspension B was slowly added dropwise to suspension A which was being vigorously stirred. The pH of the mixture was adjusted to 10.0 with sodium bicarbonate-sodium carbonate buffer solution. The mixture was then crystallized in a water bath at 60-70℃ for 20-28 hours under nitrogen protection. After the reaction was completed, the precipitate was collected by centrifugation and washed 2-3 times alternately with deionized water and anhydrous ethanol. The precipitate was then dried in a vacuum drying oven at 55-65℃ for 10-15 hours to obtain the biochar-Mg / Al-LDH-GO complex. 4) Preparation of biochar-LDH-nZVI-GO composite material: Take the biochar-Mg / Al-LDH-GO composite material prepared above, disperse it in a mixed aqueous solvent of 70% ethanol and 5% isopropanol, and form a uniform suspension C by ultrasonic treatment; under nitrogen protection and ice-water bath, slowly add an appropriate amount of FeSO4·7H2O to the suspension C and stir vigorously, and slowly add 1.0 mol / L NaBH4 to the system dropwise. React for 0.5-1.5 h, wash 2-4 times with anhydrous ethanol, and then vacuum dry at 55-65℃ to obtain the final product.

9. The application of the biochar-LDH-nZVI-GO composite material according to any one of claims 1-8 in the in-situ remediation of organic pollution in soil or water.

10. The application according to claim 9, characterized in that, The organic pollution is halogenated hydrocarbons and / or benzene series pollution; further, the halogenated hydrocarbons are trichloroethylene, and the benzene series are chlorobenzene and / or polychlorinated biphenyls.

Citation Information

Cited By

  • Papermaking sewage treatment agent and application thereof

    CN119409266A

  • Papermaking wastewater treatment agent and application thereof

    CN119409266B

  • Organic-inorganic composite repairing material for heavy metal passivation of farmland soil and preparation method of organic-inorganic composite repairing material

    CN122146309A

  • An organic-inorganic composite remediation material for heavy metal passivation in farmland soil and its preparation method

    CN122146309B